Neuregulin 1 Promotes Glutathione-Dependent Neuronal Cobalamin Metabolism by Stimulating Cysteine Uptake. (29th December 2015) - Zhang, Yiting; Hodgson, Nathaniel; Trivedi, Malav; Deth, Richard
Abstract : Neuregulin 1 (NRG-1) is a key neurotrophic factor involved in energy homeostasis and CNS development, and impaired NRG-1 signaling is associated with neurological disorders. Cobalamin (Cbl), also known as vitamin B12, is an essential micronutrient which mammals must acquire through diet, and neurologic dysfunction is a primary clinical manifestation of Cbl deficiency. Here we show that NRG-1 stimulates synthesis of the two bioactive Cbl species adenosylcobalamin (AdoCbl) and methylcobalamin (MeCbl) in human neuroblastoma cells by both promoting conversion of inactive to active Cbl species and increasing neuronal Cbl uptake. Formation of active Cbls is glutathione- (GSH-) dependent and the NRG-1-initiated increase is dependent upon its stimulation of cysteine uptake by excitatory amino acid transporter 3 (EAAT3), leading to increased GSH. The stimulatory effect of NRG-1 on cellular Cbl uptake is associated with increased expression of megalin, which is known to facilitate Cbl transport in ileum and kidney. MeCbl is a required cofactor for methionine synthase (MS) and we demonstrate the ability of NRG-1 to increase MS activity, and affect levels of methionine methylation cycle metabolites. Our results identify novel neuroprotective roles of NRG-1 including stimulating antioxidant synthesis and promoting active Cbl formation.